Stunned Myocardium as a Sequela of Acute Severe Anemia: An Adult Simulation Case for Anesthesiology Residents - David Ryusuke Okano; Bryan Ko; Marelle Giuliano; Sally Mitchell; Johnny Cartwright; Christopher Moore; Tanna Boyer (Association of American Medical Colleges, 2024)
Introduction Anesthesiologists develop anesthetic plans according to the surgical procedure, patient's medical history, and physical exams. Patients with ischemic heart disease are predisposed to intraoperative cardiac complications from surgical blood loss. Unanticipated events can lead to intraoperative complications despite careful anesthesia planning. Methods This anesthetic management simulation was developed for the anesthesiology residency curriculum during the first clinical anesthesia year (CA 1/PGY 2 residents). A total of 23 CA 1 residents participated. A 50-minute encounter focused on a 73-year-old male who presents for an elective total hip replacement and develops acute myocardial stunning in the setting of critical acute blood loss and a delay in the transportation of blood products. Results One hundred percent of the residents felt the simulation was educationally valuable in the immediate postsimulation survey (Kirkpatrick level 1). The follow-up survey showed that 100% of residents felt the simulation increased their knowledge of managing acute cardiac ischemia (Kirkpatrick level 2), and 93% felt it increased awareness and confidence in similar real-life situations that positively affected patient outcomes (Kirkpatrick level 3). Discussion Our simulation provides a psychologically safe environment for anesthesiology residents to develop management skills for acute critical anemia and cardiogenic shock and foster communication skills with a surgery team.